Training for Micrographia Alters Neural Connectivity in Parkinson's Disease - Nackaerts, Evelien; Michely, Jochen; Heremans, Elke; Swinnen, Stephan P.; Smits-Engelsman, Bouwien C. M.; Vandenberghe, Wim; Grefkes, Christian; Nieuwboer, Alice (Frontiers in Neuroscience, 2018)
Despite recent advances in clarifying the neural networks underlying rehabilitation in Parkinson’s disease (PD), the impact of prolonged motor learning interventions on brain connectivity in people with PD is currently unknown. Therefore, the objective of this study was to compare cortical network changes after six weeks of visually cued handwriting training (= experimental) with a placebo intervention to address micrographia, a common problem in PD. Twenty seven early Parkinson’s patients on dopaminergic medication performed a pre-writing task in both the presence and absence of visual cues during behavioral tests and during fMRI. Subsequently, patients were randomized to the experimental (N = 13) or placebo intervention (N = 14) both lasting six weeks, after which they underwent the same testing procedure. We used dynamic causal modeling to compare the neural network dynamics in both groups before and after training. Most importantly, intensive writing training propagated connectivity via the left hemispheric visuomotor stream to an increased coupling with the supplementary motor area, not witnessed in the placebo group. Training enhanced communication in the left visuomotor integration system in line with the learned visually steered training. Notably, this pattern was apparent irrespective of the presence of cues, suggesting transfer from cued to uncued handwriting. We conclude that in early PD intensive motor skill learning, which led to clinical improvement, alters cortical network functioning. We showed for the first time in a placebo-controlled design that it remains possible to enhance the drive to the supplementary motor area through motor learning.